PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PIGAM (PIRAMIDA KEBERAGAMAN) UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V DI SDN 1 SEMANDING - Salwa Naila Widad Aziza; Vivi Rulviana; Hartini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The 21st century era requires a generation of the nation with character, Pancasila education is very important to be implemented in all generations of the nation as a form of maintaining unity and cultural diversity in the homeland. The cultural diversity found in Indonesia is one form of heritage from ancestors that needs to be maintained and preserved. Cultural diversity in Indonesia is of many types from indigenous tribes, traditional clothing, traditional dances, traditional weapons, traditional houses and traditional musical instruments. This cultural diversity needs to be taught to students as a form of understanding of tolerance and respect for existing differences. Pancasila learning is one of the subjects that supports the growth of students' cognitive learning outcomes in the Merdeka Curriculum. The focus of this learning outcome is achieving educational goals. This study observes how much progress has occurred in learning outcomes in the field of Pancasila Education by implementing the Problem-Based Learning method, and using PIGAM (Pyramid of Diversity) resources for fifth-grade students at SDN 1 Semanding in the 2025/2026 academic year. This study is included in the Classroom Action Research category. The following implementation results demonstrate that the integration of the Problem-Based Learning strategy and the Diversity Pyramid resource in the Pancasila Education classroom resulted in significant improvements in learning achievement. In the pre-cycle phase, only 7 students met the minimum criteria (KKM), equivalent to 41.17%. In the first cycle, the number of students achieving the passing grade increased to 10, representing a percentage of 58.82%. In the second cycle, 16 students successfully achieved the passing grade, representing a percentage of 94.11%. Therefore, it can be concluded that the use of the Problem-Based Learning Model combined with the Diversity Pyramid resource in the Pancasila Education classroom effectively improved the academic achievement of fifth-grade students at SDN 1 Semanding.